The frequency and acceptance of educational technology as a learning tool among faculty members - Farnaz Shavandi; Hossein Emad Momtaz; Nastaran Moradi; Zahra Cheraghi; Masoumeh Seidi (Journal of Medical Education Development)
Background & Objective: Educational technologies improve instruction and make learning easier. They have several advantages, such as encouraging active learning, raising motivation, and improving the standard of instruction. This study aimed to determine how frequently and how well faculty members at Hamadan University of Medical Sciences used educational technology as a teaching tool. Additionally, it aimed to identify the difficulties related to online learning and collect their opinions on educational technology. Materials & Methods: By the ethical code IR.UMSHA.REC.1402.037, a cross-sectional study, was conducted between early February and early May 2023. The target population consisted of all Hamadan University of Medical Sciences faculty members, of which 139 or so were chosen by stratified random sampling from each particular school. The research instrument was a questionnaire divided into sections covering: 1) socio-demographics and occupation, 2) experience with new educational technologies, 3) a list of these technologies, and 4) questions derived from the validated Technology Acceptance Model (TAM). We utilized a multiple linear regression model to analyze the relationship between demographic variables and outcomes. We also used the chi-square test to compare proportional differences at a 95% confidence level. Results: According to the analysis, 86.33% of faculty members have integrated new educational technologies into their instruction. Wearable technology was used the least for instruction (1.44%), while mobile apps were the most common (53.96%). The majority of new educational technologies (47.48%) were used for theoretical instruction. Conclusion: Given the advantages of educational technologies, investigating how they are currently being used and creating a systematic plan for their successful implementation can benefit faculty, students, and academic institutions. This method should supplement conventional lectures.